Development of an intelligent multimodal biometric system for household appliances control - Salami, Momoh Jimoh Emiyoka (s.n, 2012)
Over the year, biometrics features which include but not limited to face, fingerprints, iris, hand geometry, palm print have been explored as a means of individual/ personal recognition. However, the existing spectra of biometric devices in real world application are contact-based devices and are mostly unimodal system. These system have not only generated issues on public health but also are susceptible to several problem such as high intra-class and interclass variation. it may be possible to enhance the multi-functionalism of these system by integrating two or more biometric. Hence, in this research, multimodal biometric system involving the integration of palmprint, teeth and voice biometrics was developed